2021
DOI: 10.1002/jcp.30588
|View full text |Cite
|
Sign up to set email alerts
|

LRRK2 and WAVE2 regulate microglial‐transition through distinct morphological phenotypes to induce neurotoxicity in a novel two‐hit in vitro model of neurodegeneration

Abstract: We report a novel in vitro classification system that tracks microglial activation state and their potential neurotoxicity. Mixed live‐cell imaging was used to characterize transition through distinct morphological phenotypes, production of reactive oxygen species (ROS), formation of reactive microglial aggregates, and subsequent cytokine production. Transwell cultures were used to determine microglial migration (control and lipopolysaccharide (LPS) treated) to glutamate pre‐stressed or healthy neurons. This t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that LRRK2 mutations could promote the progression of PD and aggravate environmental toxin-induced inflammation. 19 , 20 , 21 Meanwhile, knockout of LRRK2 gene prevents the neurotoxic effects and neuroinflammatory reactions caused by paraquat. 22 Although these studies have revealed the improving effect of LRRK2 G2019S mutation in neurotoxin-induced neuroinflammation, it is still difficult to speculate how LRRK2 is involved in the inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that LRRK2 mutations could promote the progression of PD and aggravate environmental toxin-induced inflammation. 19 , 20 , 21 Meanwhile, knockout of LRRK2 gene prevents the neurotoxic effects and neuroinflammatory reactions caused by paraquat. 22 Although these studies have revealed the improving effect of LRRK2 G2019S mutation in neurotoxin-induced neuroinflammation, it is still difficult to speculate how LRRK2 is involved in the inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%
“…The transwell insert system is widely used in studying the crosstalk activities of two different kinds of cells, wherein the influence of one cell line on another kind of cell can be avoided during the cell treatment process. For example, the transwell system, expressing the LPS-treated microglia, was utilized by Fenner et al ( 2021 ) to demonstrate the inflammatory effects of healthy neurons. Song et al ( 2012 ) also cultured microglia and neuroblastoma in the transwell system.…”
Section: Discussionmentioning
confidence: 99%
“…LRRK2 phosphorylates WAVE2, stabilizes its levels and modulates the dynamics of WAVE2-mediated phagocytic activity of macrophage cells 141 . Several subsequent reports appear to support the association of WAVE2 with PD 142 , 143 , although the mechanistic basis of WAVE2 action in the pathogenesis of PD is still unclear.…”
Section: The Association Of Wrc Dysfunction With Brain Disordersmentioning
confidence: 99%